Exploring the therapeutic properties of chinese mushrooms with a focus on their anti-cancer effects: A systemic review - Priyanka Ray; Shreya Kundu; Diptayan Paul (Elsevier, 2024)
Introduction: Mushrooms have long been integral components of traditional Chinese medicine (TCM), contributing significantly to the holistic approach to health and well-being. This review presents a critical study on mushrooms' integral role in Traditional Chinese Medicine (TCM), emphasizing their potent anticancer properties. Mushrooms have been pivotal in TCM for centuries, contributing to holistic healing practices. The article aims to comprehensively explore mushrooms' historical significance, therapeutic properties, and scientific validation within the framework of TCM, particularly their efficacy in cancer prevention and treatment. Methods: A thorough search was made through scientific electronic sources like Scopus, PubMed, ResearchGate, and Elsevier Journals to find studies on ''Medicinal mushrooms and fungus,'' ''cancer,'' ''tumor,'' ''traditional Chinese medicine,'' and ''antioxidant.'' Only entire English-language articles were used. The analysis excluded articles that did not fit the requirements. The study examined Chinese mushroom species for antioxidant, anticancer, tumor suppressive, and antibacterial properties. This article lists many mushroom species and their Chinese names. Figure 1 depicts the method in a flowchart form. Results: Ganoderma lucidum (Reishi) targets the PI3K/AKT/mTOR pathway, crucial for cell survival. Trametes versicolor, containing PSK or PSP, inhibits TNF-α-induced MMP-3 synthesis in T98G glioma cells. Lignosus rhinoceros, after 24-hour LPS stimulation, inhibits COX-2 activity, demonstrating effective in vivo anti-tumor potential. Chinese Cordyceps boosts immunological responses and reduces tumor microenvironment immunosuppression. Fomitopsis fomentarius intracellular polysaccharides suppress SGC 7091 gastric cancer cell proliferation, while extracellular polysaccharides enhance immune responses in mice. Fomitopsis pinicola inhibits vascular endothelial growth factor and may curb oxidative stress and inflammation promoting cancer. Hericium erinaceus extracts inhibit breast cancer cell proliferation in vitro and in SCID mice. Lentinan from Lentinula edodes suppresses cell growth and alters gene expression. Piptoporus betulinus inhibits cancer cell adhesion and induces apoptosis. Polyporus spp. extracts induce apoptosis and reduce tumor growth. Tumulosic acid from Poria cocos inhibits PI3K-Akt signaling in ovarian and breast cancer. Coriolus versicolor has immunomodulatory effects, suppressing TNF-α and enhancing IFN-β levels, and reducing cancer cell invasiveness directly and indirectly. Discussion: The diverse anticancer activities of various mushroom species and their compounds are evident. These include modulating PI3K/AKT/mTOR, reducing proliferation, inducing apoptosis, suppressing angiogenesis, and modulating immunity and inflammation crucial for cancer progression. These findings suggest their potential as alternative or supplementary cancer therapies, necessitating further research for understanding mechanisms, optimizing dosages, and evaluating clinical efficacy and safety, including exploring synergies with conventional treatments.